In his keeping - Banks, Maya (Banks, Maya. Slow burn series., 2015)
"Abandoned as a baby to a young wealthy couple and raised in a world of privilege, Arial has no hint of her past or who she belonged to. Her only link lies in the one thing that sets her apart from everyone else--telekinetic powers. Protected by her adoptive parents and hidden from the public to keep her gift secret, Ari is raised in the lap of luxury, and isolation. That is, until someone begins threatening her life"--